Problematika Perilaku Bidah dalam Kritik Hadis - Ahmad Isnaeni (Jurusan Tafsir Hadis Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2016)
This article aims to discuss the heretic (bid‘ah) issues related to ?adîth naration. It actually has been a topic of discussion among muslim scholars (ulama). Some of them refuse the reliability of those ?adîth narrated by the heretics, but some others maintain to receive their narration. This topic has become a polemical disputatation for the heretics are usually labelled negatively as “ahl al-ahwâ’ wa al-bida‘”, which in turns, brings them into a low level of personal degree. Interestingly, some of the heretics narrators are quoted and narrated by the major ?adîth scholars like al-Bukhârî and Muslim. This article argues that ?adîth scholars have revealed a neutral and objective position in appraising the narration of ?adîth from those accused as heretics.